High-grade myofibroblastic sarcoma in the first metacarpal: An unusual case in hand surgery - Osnaya-Moreno Humberto; Jiménez-Murat Yusef; Ceballos-Villalva Jesús Carlos; Fukumoto-Inukai Kenzo Alejandro (Chinese Journal of Plastic and Reconstructive Surgery)
Myofibroblastic sarcoma (MS) is a rare malignant soft tissue tumor characterized by myofibroblasts. It most commonly arises in the head and neck region, especially the tongue, with rare occurrences in the limbs. MS exhibits varying histopathology, ranging from low-to high-grade, with diverse subtypes showing different clinical behaviors and prognoses. This article reports the first case of high-grade MS in the hand, adding to the limited documentation of this rare condition. Here, we present the case of a 30-year-old healthy female with a year-long history of progressive shortening, mobility loss, and weakness in the first finger of the left hand. Left-hand imaging revealed a lytic, cottony tumor involving the entire first metacarpal. Following surgical resection, which included metatarsal grafting and joint reconstruction, a diagnosis of high-grade MS was confirmed based on histological manifestations and immunohistochemical staining, which was further classified as grade 2 according to the French Federation of Cancer Centers Sarcoma Group system. Postoperative radiotherapy was administered and the patient experienced a successful recovery without graft osteonecrosis. The patient regained 90% mobility and strength, without shortening, after surgical resection and radiotherapy. Six months post-surgery, the patient reported full hand functionality. MS is a rare tumor that infrequently affects bones and is often misdiagnosed owing to its controversial characteristics. The initial treatment should focus on complete resection with negative margins, followed by reconstructive surgery to preserve function. Further case studies are needed to establish standardized surgical treatment protocols.